2020
DOI: 10.3390/antiox9101013
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Oxidative Stress in the Pathogenesis and Progression of Genetic Diseases of the Connective Tissue

Abstract: Connective tissue is known to provide structural and functional “glue” properties to other tissues. It contains cellular and molecular components that are arranged in several dynamic organizations. Connective tissue is the focus of numerous genetic and nongenetic diseases. Genetic diseases of the connective tissue are minority or rare, but no less important than the nongenetic diseases. Here we review the impact of reactive oxygen species (ROS) and oxidative stress on the onset and/or progression of diseases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 304 publications
(348 reference statements)
0
24
0
Order By: Relevance
“…Few studies have been published on the potential use of target therapies against oxidative stress in patients with WBS [ 71 ]. The complexity of elastin fiber assembly creates challenges for the search for possible therapies [ 77 ].…”
Section: Role Of Oxidative Stress In Wbsmentioning
confidence: 99%
“…Few studies have been published on the potential use of target therapies against oxidative stress in patients with WBS [ 71 ]. The complexity of elastin fiber assembly creates challenges for the search for possible therapies [ 77 ].…”
Section: Role Of Oxidative Stress In Wbsmentioning
confidence: 99%
“…Most cells undergo normal cellular senescence with increasing age, while premature cellular senescence can be acutely triggered by various stressors, including ionizing radiation, hyperglycemia, and oxidative stress [ 9 , 10 , 11 ]. Oxidative stress is a damaging response and refers to excessive intracellular levels of reactive oxygen species (ROS) [ 12 ]. Previous studies reported that excess ROS can cause damage to vital biomolecules, such as proteins, lipids, and DNA; moreover, excessive molecular damage in cells might lead to cellular senescence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another factor associated with neurodegenerative diseases is the increase in oxidative stress in the CNS. Oxidative processes of cellular metabolism lead to the formation of reactive oxygen or nitrogen species (RNS), due to the partial reduction in molecular oxygen (O 2 ) by both free electrons and radicals [ 19 , 20 ]. The primary ROS products generated after the partial reduction of O 2 are singlet oxygen (1O 2 ), O 2 •− and H 2 O 2, while subsequent reactions generate hydroxyl radical (OH•) and hypochlorous acid (HOCl) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative processes of cellular metabolism lead to the formation of reactive oxygen or nitrogen species (RNS), due to the partial reduction in molecular oxygen (O 2 ) by both free electrons and radicals [ 19 , 20 ]. The primary ROS products generated after the partial reduction of O 2 are singlet oxygen (1O 2 ), O 2 •− and H 2 O 2, while subsequent reactions generate hydroxyl radical (OH•) and hypochlorous acid (HOCl) [ 19 , 20 ]. ROS and free radicals induce progressive damage to macromolecules such as DNA, lipids, carbohydrates and proteins [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%